The Court of Appeal Decision in Accent Management Ltd v CIR [2007] NZCA 230: Statutory Interpretation in New Zealand Tax Avoidance Law - Than, Tut (Auckland University of Technology, 2007)
In June 2007, the Court of Appeal in New Zealand disallowed the taxpayers appeal and decided that Trinity Scheme is a tax avoidance arrangement. The decision is significant not only for NZD3billion which is at stake but also for its jurisprudence on tax avoidance. This paper analyses the implication of Accent decision on the development of judicial approach on tax avoidance. Purposive approach of interpretation is codified in New Zealand since mid-19th century. Although New Zealand courts are not reluctant in using purposive approach in judicial reasoning, the final decisions rarely depart from literal meaning of the Act. The tension between general anti-avoidance provision and the specific provision within the Act has long been recognised by the court. The Court of Appeal in Accent proposed a judicial technique which would involve seeing tax avoidance cases in three different categories.
Keywords: Statutory interpretation; Tax avoidance; Taxation; Judiciary system